Edukasi Anemia pada Ibu Hamil Masa Pandemi Covid-19 Di Puskesmas Pembantu Tondo Kota Palu - Ni Ketut Kariani; Zulfiana; Sitti Rachma (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Anemia is a nutritional problem that needs attention and is one of the public health problems in Indonesia that can be experienced by all age groups, one of which is pregnant women. The incidence of anemia in pregnant women during the Covid-19 pandemic has increased. Based on Riskesdas 2018, the percentage of pregnant women who experience anemia is 48.9%. The purpose of this community service activity is to educate pregnant women regarding anemia during the Covid-19 pandemic. The location of this activity was carried out at the Tondo Sub Health Center, Palu City. The method used in this community service activity is in the form of lectures and discussions using leaflet media, the participants are followed by 12 pregnant women. Before the educational activity was held, participants filled out a pre-test questionnaire and then carried out education, discussion, question-answer and post-test. The results of the knowledge activities of pregnant women about anemia in pregnancy based on the results of the pre test questionnaire 8 pregnant women (67%) some pregnant women did not know about anemia in pregnancy, while based on the post test results 10 pregnant women (83%) almost all mothers already knew about what , causes, risks and how to prevent anemia in pregnancy.